Netizens Negative Sentences in the Comments Column of Najwa Shihab's Instagram Account (IG TV Posts Titled #teamganjar or #teampuan) - Andini Agustina, Syifa; Putri, Mahda (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
A negative sentence is a sentence that contains elements of negation or denial. This sentence is a denial of something. In addition to direct human speech with other humans, negative sentences can also be found from indirect speech. Examples of negative sentences in indirect speech are Articles, News, Comment columns and so on. Instagram is one of the social media that can be used to upload photos or videos that can be reached by other instagram users. Instagram is a social media that is used as an object in this study. One of the features contained in instagram is the comment field. One of the problems that will be discussed is the use of negative sentences contained in the comments column on Najwa Shihab's instagram account. The purpose of this study was to describe the markers, forms and meanings of negative sentences contained in one of the comments column Najwa Syihab instagram account. The method used in this study is a qualitative descriptive method with listen and record techniques. The Data obtained in this study comes from the comments of netizens contained on Najwa Shihab's instagram account.